2014
DOI: 10.1111/j.2047-2927.2014.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression signature of early stages of the germ line supports the pre‐meiotic origin of human spermatogenic failure

Abstract: Summary The molecular basis of spermatogenic failure (SpF) is still largely unknown. Accumulating evidence suggests that a series of specific events such as meiosis, are determined at the early stage of spermatogenesis. This study aims to assess the expression profile of pre‐meiotic genes of infertile testicular biopsies that might help to define the molecular phenotype associated with human deficiency of sperm production. An accurate quantification of testicular mRNA levels of genes expressed in spermatogonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Many of these genes are also directly involved in spermatogenesis, such as the HILS1 gene that remodels chromatin during gamete production [ 50 ], the KAT7 and ICAM2 genes expressed in Sertoli cells [ 51 , 52 ], the TCAM1 gene expressed in spermatocytes [ 53 ], the SLC26A3 gene that is essential for sperm capacitation [ 54 ], and the RAD18 gene that plays a crucial role in genome maintenance during sperm production [ 55 ]. Other important genes are the FBXO32 (Chr14/17.83–18.51Mb) and EBF2 (Chr08/73.91-75Mb) genes related to infertility and hypogonadism in men, respectively [ 56 , 57 ], and the GH1 gene (Chr19/48.69–49.21Mb) associated with seminal characteristics and sexual behavior in cattle [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many of these genes are also directly involved in spermatogenesis, such as the HILS1 gene that remodels chromatin during gamete production [ 50 ], the KAT7 and ICAM2 genes expressed in Sertoli cells [ 51 , 52 ], the TCAM1 gene expressed in spermatocytes [ 53 ], the SLC26A3 gene that is essential for sperm capacitation [ 54 ], and the RAD18 gene that plays a crucial role in genome maintenance during sperm production [ 55 ]. Other important genes are the FBXO32 (Chr14/17.83–18.51Mb) and EBF2 (Chr08/73.91-75Mb) genes related to infertility and hypogonadism in men, respectively [ 56 , 57 ], and the GH1 gene (Chr19/48.69–49.21Mb) associated with seminal characteristics and sexual behavior in cattle [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Dicer1, a protein necessary for miRNA processing and Dnd1, a protein implicated in the protection of mRNAs from miRNAs, are essential for the completion of spermatogenesis 3 11 22 . We have previously demonstrated that low spermatogenic efficiency in infertile men is accompanied by an altered gene expression capacity of germ-cells, which contributes to unsuccessful sperm production 23 24 , thus, in this context, it is reasonable to study the cellular miRNA expression behavior, as a likely mechanism of gene expression regulation, in spermatogenic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the cellular miRNA content of testicular germ-cells, we considered the fact that the miRNA expression levels per tubule are the result of a composite of different cell types, as we have previously described for determining mRNA germ-cell content 23 24 . Therefore, we calculated the miRNA expression levels per germ-cell by adjusting total expression levels to the proportion of germ-cell stages that specifically express the miRNAs in a seminiferous tubule, to correct for the actual amount of expressing germ-cells in each particular sample.…”
Section: Methodsmentioning
confidence: 99%
“…In humans, knowledge about the molecular processes that control spermatogenesis is still limited. Recent gene expression studies have shown that human spermatogenesis is controlled by a complex network of molecular pathways ( Bonache et al, 2014 ; Feig et al, 2007 ; Shafipour et al, 2014 ). However, these studies investigated expression changes in entire testicular biopsies from healthy and subfertile men.…”
Section: Introductionmentioning
confidence: 99%